A Forty Five Years Female Patient with Sclerosteosis - Ahmed, Shamim; Kader, Md Abdul; Ahmed, Quazi Mamtaz Uddin; Shahin, Abu; Azad, Md Abul Kalam; Banik, Jayanta; Mojumdar, Shoayb Momen; Rahman, Mohammad Ferdous Ur; Ara, Rowsan; Haq, Syed Atiqul (Journal of Medicine, 2010)
Sclerosteosis is a rare autosomal recessive disorder, characterized by progressive, generalized bony overgrowth of the calvarium and mandible with cranial nerve entrapment and raised intracranial pressure, and abnormalities of the digits. Due to narrowing of the foramina of the cranial nerves, facial nerve palsy, hearing loss and atrophy of the optic nerves can occur. It is clinically and radiologically very similar to van Buchem disease, both of which shows generalized hyperostosis and sclerosis leading to a markedly thickened and sclerotic skull, with mandible, ribs, clavicles and also long bones. Van Buchem disease is differentiated from sclerosteosis by the absence of hand malformations and a large stature. Here we describe a case of a 45 years-old-female presented with progressive enlargement of right side of mandible, continuous pain in the right side of the face, right sided lower motor type of facial palsy, bilateral sensory neural type of hearing loss along with polydactyly and syndactyly. The final diagnosis of sclerosteosis was made by clinical features and radiological findings and exclusion of other causes of hyperosteosis. The particular interest of this paper is to present a case of sclerosteosis, and to demonstrate the differences between that entity and other sclerosing diseases of bone. Keywords: Sclerosteosis; van Buchem disease; Hyperosteosis DOI: 10.3329/jom.v11i2.5477 J MEDICINE 2010; 11 : 207-211